34. PATIENT’S EXPERIENCE DURING INPATIENT TREATMENT AT SOME HEALTHCARE FACILITIES IN VINH PHUC PROVINCE 2024 (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the experience of inpatients at some medical facilities in Vinh Phuc province in 2024.Method: A cross-sectional study combining quantitative and qualitative methods, with a sample size of 374 subjects. The research tools included semi-structured questionnaires and in-depth interview guidelines.Results: The study results indicate that 61.8% of patients rated their experience as positive, with an average experience score of 8.7/10. Factors such as the attentiveness, guidance of healthcare staff, and quality of care significantly influenced patient experience. Approximately 64.7% of survey participants stated that they would definitely return and recommend the hospitals to others.Conclusion: The proportion of patients with a positive experience is relatively high; however, further improvements in certain areas are needed to enhance service quality.
Keywords: Patient experience; inpatient; rehabilitation